Tinjauan Yuridis Larangan Praktik Lesbian Gay Biseksual Transgender And Queer (LGBTQ) di Indonesia Berdasarkan Pasal 28b Ayat 1 Undang-Undang Dasar 1945 - Irvan, Irvan; Hariansah, Syafri; Tribuana, Robi Rendra (JYRS: Journal of Youth Research and Studies, 2024)
The prohibition of LGBTQ practices in Indonesia based on article 28B paragraph 1 of the 1945 Constitution is a controversial issue. The article reads, "Everyone has the right to form a family and continue their offspring through legal marriage." The interpretation of this article gives rise to differences of opinion, between those who support and those who reject the prohibition. Supporters of the ban argue that LGBTQ practices conflict with Indonesia's religious and cultural values. They argued that marriage should only be carried out by husband and wife pairs consisting of a man and a woman. Meanwhile, those who oppose the ban argue that LGBTQ practices are human rights that must be respected. They argue that everyone has the right to freely determine their sexual orientation and gender identity. Legal provisions regarding the prohibition of LGBTQ practices in Indonesia are still unclear. However, several regional regulations have prohibited this practice, such as in South Tangerang City, Depok City and Bogor Regency. Ultimately, decisions regarding the ban on LGBTQ practices in Indonesia are the authority of the government. The government needs to consider various aspects, including legal, religious, cultural and human rights aspects, in making this decision.